Microstructure and hot corrosion behavior of Co–Si modified aluminide coating on nickel based superalloys. (November 2015) - He, Haiyan; Liu, Zongjie; Wang, Wan; Zhou, Chungen
Highlights: Co–Al–Si coating was obtained by pack cementation process. The coating has good hot corrosion resistance. The mechanism of Si during the hot corrosion of the coating has been proposed. Abstract: Co–Si modified aluminide coating on nickel based superalloys was prepared by pack cementation process, then microstructure and hot corrosion resistance were studied. The mass gain of Co–Si modified aluminide coating is 0.32 mg/cm 2 after hot corrosion at 1173 K for 100 h. Si can boost the hot corrosion resistance by improving the formation of Al2 O3 . SiO2 has low solubility over a wide range of salt acidity and good stability in the melting Na2 SO4 + NaCl, preventing rapid corrosion attack and prohibiting the high fluxing rate.